Social Innovation for Sustainability Transformation and its Diverging Development Paths in Marginalised Rural Areas. Issue 2 (26th March 2021) - Kluvankova, Tatiana; Nijnik, Maria; Spacek, Martin; Sarkki, Simo; Perlik, Manfred; Lukesch, Robert; Melnykovych, Mariana; Valero, Diana; Brnkalakova, Stanislava
Abstract: Social innovation is perceived as a collaborative response from civic society actors to societal challenges and as such is increasingly being recognised as a driver for sustainable development. Social innovation promotes civic values, particularly in marginalised rural areas that are often struggling with biophysical and market limits, as well as shortages of public funding. In order to identify diverging development paths (DDPs) for social innovation, in this article, we use two large sets of empirical material from the SIMRA research project. First, for meta‐analyses of social innovation in diverse situations and contexts, we use 211 validated social innovation examples. Second, we rely on 11 in‐depth cases to reflect on the contexts and dimensions of social innovation. The elaboration of conceptualisation and deductive analyses result in the creation of a typology of social innovation DDPs, with four DDPs identified and explained. The article provides an improved understanding of how social innovation emerges and develops and how to capture processes and resulting changes in marginalised rural areas in order to turn such areas' diversity into strengths. An important conclusion is that social innovation involves both local and external actors, yet cannot develop without specific internal local activity and local knowledge.